Bank equity connections, intellectual property protection and enterprise innovation: A bank ownership perspective - Xing Liu; Shuiquan Jiang (China Journal of Accounting Research, 2016)
This study investigates the effects of bank equity connections and intellectual property protection on enterprises' innovation behavior, and the regulating effect of intellectual property protection on the relationship between bank equity connections and innovation. In general, bank equity connections and intellectual property protection not only significantly increase innovation input, but also improve innovation performance. However, the efficiency of bank equity connections is influenced by the heterogeneity of enterprises and the value orientation of the subjects. Bank equity connections have a more significantly positive effect on innovation in private and central enterprises, whereas the principal-agent problem and government intervention may weaken the marginal contribution of bank equity connections to the innovation of local state-owned enterprises. Bank equity connections and intellectual property protection are complementary in promoting enterprise innovation. Not only are the combined effects of bank equity connections and intellectual property protection greater than the individual effects, but when the latter is relatively weak, the former's positive effect on innovation is obviously weakened and may even crowd out innovation.
Keywords: 650; Bank equity connections; Intellectual property protection; Corporate innovation; Innovation performance